2017
DOI: 10.1080/08956308.2017.1301001
|View full text |Cite
|
Sign up to set email alerts
|

Creating and Capturing Value Through Sustainability

Abstract: Recent research and practice have shown that business model innovation can be one way to create and capture new value and drive production and consumption toward sustainability. However, business model tools typically do not create a space to consider how sustainability concerns may be integrated into the innovation process. To address this gap, this article describes a tool that can help companies identify new opportunities to create and capture value through sustainability by analyzing value captured and unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 20 publications
0
77
0
Order By: Relevance
“…However, it is still not easy for the interviewees to identify all economic, social and environmental value of each PSS business model within a short interview. We therefore used a poster which is part of the Sustainable Value Analysis Tool (Yang et al, 2017b) to inspire them to answer the questions, shown in Figure 2. The reason for using the data collection tool in our interviews was that the visualised format greatly increased the engagement of the interviewees, triggered more structured and detailed data and therefore improved the data collection.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, it is still not easy for the interviewees to identify all economic, social and environmental value of each PSS business model within a short interview. We therefore used a poster which is part of the Sustainable Value Analysis Tool (Yang et al, 2017b) to inspire them to answer the questions, shown in Figure 2. The reason for using the data collection tool in our interviews was that the visualised format greatly increased the engagement of the interviewees, triggered more structured and detailed data and therefore improved the data collection.…”
Section: Data Collectionmentioning
confidence: 99%
“…Tools and methods for business modelling are scarce and rarely elevate sustainability as a driver ( Geissdoerfer et al., 2018 ). In response, recent academic work has focused on tool development to support business model innovation at the organisational level ( Bocken et al., 2013 ; Breuer et al., 2018 ; Geissdoerfer et al., 2016 ; Joyce and Paquin, 2016 ; Yang et al., 2017 ). While research has focused on design of sustainable business models to some extent ( Breuer et al., 2018 ), there are few examples of successful implementation of sustainable business models ( Ritala et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the complexity of the proposed benchmarking perspective could hinder its wide-spread application across sectors. On the other hand, approached sustainability theory from the perspective of value captured/uncaptured with a purpose of developing a sustainable value analysis tool [322,323]. In one study, the value uncaptured concept was developed and tested in six case studies to ensure validity of concept, whereas, in the next study, the concept was turned into a sustainable value analysis tool that would aid organizations with identification of value uncaptured along the life cycle of a product.…”
Section: Past Lean-based Sustainability Assessment Frameworkmentioning
confidence: 99%